GPU Computing and Applications - Cai, Yiyu (Springer, 2015)
Graphics Processing Unit (GPU) technology is playing an important role in com puting today. This book presents a collection of state-of-the-art research on GPU computing and their applications. The major part of this book is selected from the work submitted to the 2013 Symposium on GPU Computing and Applications jointly organized by the Institute for Media Innovation of Nanyang Technological University, and NVIDIA Corporation (South East Asia). The book addresses the fundamental issues in GPU computing with a focus on big data processing. Three major domains of GPU applications are covered in the book including (1) Engineering design and simulation; (2) Biomedical Sciences; and (3) Interactive & Digital Media...